Benefits of neutral polysaccharide from rhizomes of Polygonatum sibiricum to intestinal function of aged mice - Li, Li-Xia; Feng, Xin; Tao, Meng-Ting; Paulsen, Berit Smestad; Huang, Chao; Feng, Bin; Liu, Wei; Yin, Zhong-Qiong; Song, Xu; Zhao, Xinghong; Liang, Xiao-Xia; Yin, Li-Zi; et al. (Frontiers in Nutrition, 2022)
One purified neutral polysaccharide fraction was obtained from the rhizome of Polygonatum sibiricum by DEAE ion exchange and gel chromatography. Structure elucidation was performed by methanolysis, methylation, FT-IR and NMR. The results indicated that PSP-NP was composed of 1,4-β-D-Gal,1, 4, 6-β-D-Gal, T-α-D-Man,1, 4-α-D-Glc and T-α-D-Glc with a molecular weight of 43.0 kDa. We supplied this polysaccharide to aged mice and found it is of benefits to intestinal functions, as indicated by better tissue integrity and motility, improved oxidative stress and inflammation, reduced intestinal permeability and serum LPS level, as well as balanced gut microbial composition and short-chain fatty acids production. These results display a novel Polygonatum sibiricum polysaccharide to improve the intestinal func-tion of aged mice, which provides pieces of evidence for its further development and utilization.